MicroRNAs in the Progress of Diabetic Nephropathy: A Systematic Review and Meta-Analysis. (7th March 2019) - Wang, Li-ping; Gao, Yu-zhen; Song, Bin; Yu, Guo; Chen, Hui; Zhang, Zhen-wen; Yan, Cai-feng; Pan, Yun-long; Yu, Xiao-yan
Abstract : Background . We conducted a systematic review and meta-analysis of existing literature to evaluate the different outcomes of microRNAs (miRNAs) in diabetic nephropathy (DN), including urinary albumin excretion rates, urinary albumin creatinine rates, glomerular filtration rate, HbAc1, and creatinine. Methods . Electronic databases including PUBMED, MEDLINE, and EMBASE were searched for eligible publications to July 2018. The following comparisons between treatment groups were included: normal group versus DN group; control group versus micro/macroalbuminuria group. Results . Twelve eligible studies that included 2500 participants were finally recruited in this meta-analysis. Fifteen miRNAs (miRNA-21, miRNA-181b, miRNA-194, miRNA-30, miRNA-215, and others) were upregulated whereas seven miRNAs (miRNA-26a, miRNA-126, miRNA-424, miRNA-574-3p, miR-223, miR-155, and miR-192) were downregulated in the DN group compared with control groups. The miR-133b, miR-342, miR-30, miR-192, miR-194, and miR-215 were significantly correlated in urinary albumin excretion rates (r=0.33, 95% CI= 0.26-0.39). miR-192, miR-217, miR-15b, miR-34a, and miR-636 were correlated with urinary albumin creatinine rates (r=0.69; 95% CI=0.12-0.92), while miR-133b, miR-345, miR-33, miR-326, miR-574-3p, miR-126, miR-217, miR-15b, miR-34a, and miR-636 were significantly correlated with HbAc1 (r =0.23, 95% CI = 0.15-0.31). There were twelve miRNAs that were closely related to the glomerular filtration rate (r=0.28, 95% CI =0.21-0.34). Creatinine (r=0.33, 95% CI = 0.22-0.40) was significantly different between normal and DN groups. Conclusions . The meta-analysis acquired the correlations between miRNAs and outcomes including UAER, UACR, eGFR, HbAc1, and creatinine in DN. It suggested that miRNAs may participate in the pathogenesis of DN process.